Clonorchis sinensis calcium-binding protein Cs16 causes acute hepatic injury possibly by reprogramming the metabolic pathway of bone marrow-derived monocytes - Li, Qi; Li, Xiao; Kan, Shuo; Zhu, Ting-Jun; Li, Chang; Du, Xin-Yue; Wang, Xin; Yan, Hui-Bo; Wu, Chen-Yun; Chen, Guang-Jie; Qian, Men-Bao; Yan, Min; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Clonorchis sinensis infection results in various complications in the liver and biliary systems, which is a neglected tropical disease in Eastern Asia. In this study, we report that C. sinensis calcium-binding protein Cs16 activates host immune cells and induces immunopathology in liver. Cs16 localizes in the tegument and gut of C. sinensis.Humans and mice with C. sinensis infection exhibited increased levels of anti-Cs16 specific antibody. Using the bile duct injection technique, we found that Cs16 induced obvious inflammation and hepatic necrosis in vivo. Cs16 treatment caused the upregulation of inflammatory cytokines in innate immune cells. Moreover, Cs16treated monocytes relied more on the glycolytic metabolic pathway. Our findings suggest Cs16 is a potential pathogenic factor derived from C. sinensis adult worm. By reprogramming the metabolic pathway of innate immune cells, Cs16 triggers proinflammatory responses in the liver, and therefore, Cs16 is a potential target for the prevention and treatment of clonorchiasis.